FGF1 protects FGFR1-overexpressing cancer cells against drugs targeting tubulin polymerization by activating AKT via two independent mechanisms - Szymczyk, Jakub; Sochacka, Martyna; Chudy, Patryk; Opalinski, Lukasz; Otlewski, Jacek; Zakrzewska, Malgorzata (Frontiers in Oncology, 2022)
Cancer drug resistance is a common, unpredictable phenomenon that develops in many types of tumors, resulting in the poor efficacy of current anticancer therapies. One of the most common, and yet the most complex causes of drug resistance is a mechanism related to dysregulation of tumor cell signaling. Abnormal signal transduction in a cancer cell is often stimulated by growth factors and their receptors, including fibroblast growth factors (FGFs) and FGF receptors (FGFRs). Here, we investigated the effect of FGF1 and FGFR1 activity on the action of drugs that disrupt tubulin polymerization (taltobulin, paclitaxel, vincristine) in FGFR1-positive cell lines, U2OS stably transfected with FGFR1 (U2OSR1) and DMS114 cells. We observed that U2OSR1 cells exhibited reduced sensitivity to the tubulin-targeting drugs, compared to U2OS cells expressing a negligible level of FGFRs. This effect was dependent on receptor activation, as inhibition of FGFR1 by a specific small-molecule inhibitor (PD173074) increased the cells’ sensitivity to these drugs. Expression of functional FGFR1 in U2OS cells resulted in increased AKT phosphorylation, with no change in total AKT level. U2OSR1 cells also exhibited an elevated MDR1 and blocking MDR1 activity with cyclosporin A increased the toxicity of paclitaxel and vincristine, but not taltobulin. Analysis of tubulin polymerization pattern using fluorescence microscopy revealed that FGF1 in U2OSR1 cells partially reverses the drug-altered phenotype in paclitaxel- and vincristine-treated cells, but not in taltobulin-treated cells. Furthermore, we showed that in U2OSR1 cells, FGF1, through activation of FGFR1, reduces caspase 3 and 7 activity and PARP cleavage, preventing taltobulin-induced apoptosis. Next, using specific kinase inhibitors, we investigated which signaling pathways are responsible for the FGF1-mediated reduction of taltobulin cytotoxicity. We found that AKT kinase is a key factor in FGF1-induced cell protection against taltobulin in U2OSR1 and DMS114 cells. Interestingly, only direct inhibition of AKT or dual-inhibition of PI3K and mTOR abolished this effect for cells treated with taltobulin. This suggests that both canonical (PI3K-dependent) and alternative (PI3K-independent) AKT-activating pathways may regulate FGF/FGFR1-driven cancer cell survival. Our findings may contribute to the development of more effective therapies and may facilitate the prevention of drug resistance in FGFR1-positive cancer cells.